The uncanny garden. Jardin-forêt at Bibliothèque nationale de France - Salwa, Mateusz (Aesthetic Investigations, 2015)
The paper is an analysis of the garden at the National Library in Paris. The garden (Jardin-foret) is desribed as uncanny for it belongs to a long tradition of gardening but at the same time it turns out to be its opposite. The uncanny effect seems to stem from the tension between artificiality and naturalness which is at least partly responsable for the lack of enthusiasm towards the garden as it is proved by a quotation from W.G. Sebald's novel 'Austerlitz'.